ANALISIS PELAYANAN CHECK-IN PENUMPANG INTERNASIONAL TERMINAL 3 BANDARA SOEKARNO-HATTA DALAM PERSPEKTIF NEW PUBLIC MANAGEMENT (NPM) - Vayla Aisya Naldzhieva Anwar; lusia Astrika (Journal of Politic and Government Studies, 2026)
International passenger check-in services at airports are a form of public service involving multiple non-governmental actors and are expected to operate efficiently and measurably. The governance of public services in the air transportation sector has increasingly adopted New Public Management (NPM) as a guiding approach. However, the implementation of NPM affects not only technical and performance-related aspects of service delivery, but also raises questions regarding the position and role of the state in safeguarding the public interest. This study aims to analyze the implementation of NPM by the Directorate General of Civil Aviation of the Ministry of Transportation in the governance of international passenger check in services at Terminal 3 of Soekarno-Hatta International Airport. This research employs a descriptive qualitative approach, with data collected through interviews, direct observations at Terminal 3, and document analysis. The research subjects consist of DGCA, Asiana Airlines, PT JAS, and international passengers who used Asiana Airlines’ check-in services. The findings reveal that the implementation of NPM is reflected in a governance pattern that emphasizes operational efficiency, performance measurement, and the active involvement of non-governmental actors as the primary service providers. The state primarily performs regulatory and supervisory functions, while daily service operations are carried out by airlines and ground handling companies, contributing to a more orderly and responsive check-in process in an international airport setting. Despite improvements in service orderliness and performance, the emphasis on efficiency poses challenges in maintaining an inclusive public service orientation. The state tends to assume the role of performance controller, whereas considerations of justice, equitable access, and protection for diverse service users remain insufficiently integrated into the service evaluation framework.